Tribo-mechanical properties and cellular viability of electrochemically treated Ti-10Nb and Ti-20Nb alloys - Luz, Aline R.; Lima, Gabriel G. de; Santos Jr, Emanuel; Pereira, Bruno L.; Sato, Hebert Hiroshi; Lepienski, Carlos M.; Lima, Daniel B.; Laurindo, Carlos; Grandini, Carlos R. [UNESP]; Kuromoto, Neide K. (Elsevier B.V., 2019)
A number of researches have been concerned about the development of beta-type titanium alloys because they can present good biocompatibility, non-cytotoxicity, suitable mechanical and corrosion resistance behavior. However, due to their chemical inertness property, the surfaces of the novel Ti alloys must be modified by different methods to improve their bioactivity. This work is focused on the electrochemical surface modification of Ti-10Nb and Ti-20Nb alloys by Plasma Electrolytic Oxidation (PEO) method in 1.0 M H3PO4 electrolyte at 250 V. X-Ray diffraction showed that both binary Ti-Nb alloys are mainly composed of (alpha+beta) phase. The PEO treatment led to producing rough and thick titanium and niobium oxides films on the Ti-Nb alloys. The oxide films produced on the Ti-10Nb alloys have the anatase structure, whereas those formed on the Ti-20Nb alloy have an amorphous structure observed by Raman Spectroscopy. Hardness and elastic modulus were measured by instrumented indentation. Both oxide films are harder than their substrates (4.0-6.0 GPa) and have reduced elastic modulus values (100-110 GPa) compared to cp-Ti (reference). Linear reciprocating tests were employed to study the surface wear resistance of the samples. Among the non-treated samples, the Ti-10Nb alloy presented a better wear performance. In addition, the titanium and niobium oxides films formed on the Ti-10Nb alloy presented the most resistant surfaces. In relation to the cellular viability evaluation, the oxide films produced on both Ti-Nb alloys did not show any sign of cytotoxicity. Indeed, the porosity, roughness and chemical composition of the resulting titanium and niobium oxides films were able to promote osteoblast cells attachment and proliferation on their surfaces. Based on these findings, the PEO electrochemical treatment on Ti-10Nb alloy can form porous oxides coating and could be used as a reference line for manufacturing more wear resistant and non-cytotoxic surfaces to biomedical applications. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Titanium alloys; Oxidation; Coatings; Cytotoxicity tests; Mechanical properties; Wear